High resolution imaging and quantification of the nailfold microvasculature using optical coherence tomography angiography (OCTA) and capillaroscopy: a preliminary study in healthy subjects - Dong, Li-Bin; Wei, Ying-Zhao; Lan, Gong-Pu; Chen, Jia-Tao; Xu, Jing-Jiang; Qin, Jia; An, Lin; Tan, Hai-Shu; Huang, Yan-Ping (Quantitative imaging in medicine and surgery, 2022)
A wide range of diseases, such as systemic sclerosis, can be diagnosed by imaging the nailfold microcirculation, which is conventionally performed using capillaroscopy. This study applied optical coherence tomography angiography (OCTA) as a novel high resolution imaging method for the qualitative and quantitative assessment of the nailfold microvasculature, and compared OCTA imaging with capillaroscopy. For qualitative assessment, high resolution OCTA imaging was used to achieve images that contained a wide field of view of the nailfold microvasculature through mosaic scanning. OCTA imaging was also used to observe the characteristic changes in the microvasculature under external compression of the upper arm. For quantitative evaluation, the capillary density and the capillary diameter of the nailfold microvasculature were assessed with both OCTA and capillaroscopy by repeated measurements over 2 days in 13 normal subjects. The results were analyzed using the intraclass correlation coefficient (ICC). OCTA imaging showed the typical nailfold microvasculature pattern, part of which was not directly seen with the capillaroscopy. OCTA imaging revealed significant changes in the nailfold microvasculature when a large external pressure was applied via arm compression, but no significant changes were observed using capillaroscopy. The capillary density measured by OCTA and capillaroscopy was 6.8±1.5 and 7.0±1.2 loops/mm, respectively, which was not significantly different (P=0.51). However, the capillary diameter measured by OCTA was significantly larger than that measured using capillaroscopy (19.1±2.5 13.3±2.3 µm, P<0.001). The capillary diameter measurements using OCTA and capillaroscopy were highly reproducible (ICC =0.926 and 0.973, respectively). While the capillary diameter measured with OCTA was significantly larger, it was rather consistent with the diameter measured using capillaroscopy (ICC =0.705). This study demonstrated that OCTA is a potentially viable and reproducible tool for the imaging and quantification of the capillaries in the nailfold microvasculature. The results of this study provide a solid basis for future applications of OCTA in qualitative and quantitative assessment of nailfold microcirculation .